COMMUNITY STRUCTURE ANALYSIS AND CARBON STOCK ESTIMATION OF MANGROVE IN CIREBON COASTAL AREA - Krishna Ramadhan, Tsanny
Community structure can describe the composition species and their abundance in a community. Each species has different characteristics and potential stored carbon stocks. The purpose of this research was to determine community structure, potential stored carbon stocks, mangrove cover area, and distribution of mangrove health. This research use Sentinel-2 image data and field measurement data of mangrove. Purposive sampling technique was used to determine the measurement stations and sample plots. Line transects and plot methods are used to take the population in a community. Species identification, canopy cover percentage measurement, and trunk diameter measurements. Carbon stock estimation using non-destructive method calculated based on allometric equation. The results showed that the area of mangrove cover in Cirebon Coastal was 640,25 ha. The distribution of mangrove health in very good category with Normalized Difference Vegetation Index (NDVI) value range of 0.72 – 0.92 has a very high canopy density and a good category with NDVI value range of 0.42–0.72 has a fairly high canopy density with a coefficient of determination of 0.568. Three mangrove species were found in 6 stations including Avicennia marina, Avicennia alba, Rhizophora mucronata. Importance Value Index (IVI) is the accumulation of relative density, relative frequency, and relative dominance. So that the maximum IVI value can reach 300 Avicennia marina species dominate and play a dominant role in providing food sources, play a role in the nitrien cycle, and become the main producer in the mangrove ecosystem. At the tree level, Avicennia marina species dominates in KJ1 Station with an INP of 300 %. At the sapling level, Avicennia marina species dominates in KJ1 Station with an INP of 219.21 %. At the seedling level, Avicennia marina species dominates in TS1 Station with an INP of 159.35 %. The best condition of mangrove forest is in TS2 Station with a canopy density percentage of 89.24 %. Carbon stock in all measurement stations ranged from 52.74-99.67 tons/ha. TS2 station has the highest carbon storage of 99.67 tons/ha.